Synthesis of ZnO/Cu micro and nanostructures via a vapor phase transport method using different tube systems - Kamalianfar, Ahmad; Shaari, Abdul Halim; Zak, Ali Khorsand (Elsevier, 2014)
ZnO micro and nanostructures were grown on copper coated silicon substrates using two different systems: an opened system (both ends opened tube) and a closed system (one closed end tube). The thermodynamic conditions of the systems made a significant difference in boundary layer and super-saturation between the systems. The results indicate that diffusion of the gaseous species through the boundary layers at low and high pressures controls the final formation of the morphologies. The ZnO nanostructures which have been grown in a restricted place have larger diameters and lengths. The structure of the products was analyzed by X-ray diffractometer (XRD) and it was found that the good crystalline quality of the samples was obtained in a closed system. To study the optical properties, photoluminescence (PL) and ultra violet–visible (UV–vis) spectroscopy were employed. It was observed that a decrease in the growth temperature of the opened system caused a broad and dominant visible emission covering the blue and green emission in the PL spectra.